2022
DOI: 10.3389/fpubh.2022.1007053
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence on structural racism as a driver of racial inequities in COVID-19 mortality

Abstract: ObjectiveThis study contributes to the literature by empirically testing the extent to which place-based structural racism is a driver of state-level racial inequalities in COVID-19 mortality using theoretically-informed, innovative approaches.MethodsCDC data are used to measure cumulative COVID-19 death rates between January 2020 and August 2022. The outcome measure is a state-level Black-White (B/W) ratio of age-adjusted death rates. We use state-level 2019 administrative data on previously validated indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…To better align measurement strategies with core tenets of structural theories, a growing chorus of scholars recommend that quantitative research on the health consequences of structural oppression use latent variable approaches , which are well‐suited for minimizing measurement error and capturing unobserved, complex systems such as structural racism and structural sexism 9,20,55 . Indeed, several recent population health studies have demonstrated the utility of confirmatory factor analysis to estimate latent measures of state‐level and county‐level structural racism (using observed, reflective indicators in housing, educational, economic, political, and criminal–legal domains) 30,37,57 . Consistent with the idea that structural racism involves a multifaceted, interconnected system, these studies used latent measurement approaches to explicitly model relationships among the multisectoral reflective indicators of structural racism.…”
Section: Recommendation 2: Develop Novel Theory‐driven Empirically Ba...mentioning
confidence: 99%
See 4 more Smart Citations
“…To better align measurement strategies with core tenets of structural theories, a growing chorus of scholars recommend that quantitative research on the health consequences of structural oppression use latent variable approaches , which are well‐suited for minimizing measurement error and capturing unobserved, complex systems such as structural racism and structural sexism 9,20,55 . Indeed, several recent population health studies have demonstrated the utility of confirmatory factor analysis to estimate latent measures of state‐level and county‐level structural racism (using observed, reflective indicators in housing, educational, economic, political, and criminal–legal domains) 30,37,57 . Consistent with the idea that structural racism involves a multifaceted, interconnected system, these studies used latent measurement approaches to explicitly model relationships among the multisectoral reflective indicators of structural racism.…”
Section: Recommendation 2: Develop Novel Theory‐driven Empirically Ba...mentioning
confidence: 99%
“…Findings from a study by Brown, Kamis, and Homan showed that a multisectoral latent measure of state-level structural racism provided a better model fit and accounted for more variation in Black-White inequities in COVID-19 mortality than individual indicators as well as a summative index of structural racism. 30 In addition, Chantarat and colleagues have contributed to the literature by using latent class analysis to identify distinct typologies of multisectoral structural racism and linking them to racialized birth outcomes. 58,59 Collectively, these studies point to promise of latent measurement approaches for advancing the scientific literature on the impact of structural oppression on health.…”
Section: Use Latent Measuresmentioning
confidence: 99%
See 3 more Smart Citations